An Analysis of Information Technology Governance Using COBIT 2019: A Case Study of the ICT Unit at Tadulako University - Armin, Magfirah Di’iznania; Ritchi, Hamzah; Tanzil, Nanny Dewi (Budapest International Research and Critics University, 2025)
The rapid advancement of information technology (IT) requires educational institutions to implement effective IT governance aligned with organizational business strategies and operations. This study aims to evaluate the capability level of IT governance at the Information and Communication Technology Unit (UPT TIK) of Tadulako University using the COBIT 2019 framework, with a focus on two specific processes: APO12 (Managed Risk) and APO13 (Managed Security). A mixed-methods approach was employed, including data collection through observations, interviews, and questionnaires. The Guttman scale and capability level calculations were used for analysis. The findings indicate that the current capability level for APO12 is at level 2, and APO13 is at level 1, whereas the desired target for both is level 4. This significant gap highlights the need for improvements in IT governance. Strategic recommendations based on the COBIT 2019 guidelines are proposed to help the institution achieve its target capability levels.